Website-Based Online Job Training Application Design Using the Unified Modeling Language - Batubara, Supina; Wahyono, Teguh; Khaliq, Abdul; Lubis, Yuli Ennisa (International Conference on Sciences Development and Technology, 2022)
Community demographic data based on work shows that there is a lot of work done by the community. This proves that the community's potential in the aspect of community resources is very good, but in the data it can also be seen that some people do not have a job or what we usually call unemployed. Unemployment rates will increase if proper evaluation is not carried out and will have a negative impact on community resources that are already good. So that unexpected things do not happen, we should dig up community data and manage existing community resources so that we can reduce unemployment so that it has a positive impact on increasing people's income. The purpose of this research is to build a job training application that can be used to collect data on skills and improve the skills possessed by the community while at the same time knowing the concept of improving digital community resource management that can be done and provide analysis of the application of online information communication. Job training applications are designed using the Unified Modeling Language (UML) and by utilizing Massive Open Online Course (MOOC) technology, sophisticated computer simulation technology with massive open online course techniques, fast-adapting computer engineering education models.